2002
DOI: 10.1046/j.1471-4159.2002.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue transglutaminase differentially modulates apoptosis in a stimuli‐dependent manner

Abstract: Tissue transglutaminase is a unique member of the transglutaminase family as it not only catalyzes a transamidating reaction, but also binds and hydrolyzes GTP and ATP. Tissue transglutaminase has been reported to be pro-apoptotic, however, conclusive evidence is still lacking. To elucidate the role of tissue transglutaminase in the apoptotic process human neuroblastoma SH-SY5Y cells were stably transfected with vector only (SH/pcDNA), wild-type tissue transglutaminase (SH/tTG) and tissue transglutaminase that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
107
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(112 citation statements)
references
References 73 publications
3
107
1
Order By: Relevance
“…In this study we demonstrate that when tTG is localized mostly in the cytosol, it facilitates apoptosis. Further, and in agreement with a previous study (15), we found that the transamidating activity of tTG is necessary for its pro-apoptotic activity in the cytosol. Both membrane and nuclear-localized wild-type tTG did not affect apoptosis, even though thapsigargin treatment resulted in a significant increase in the transamidating activity of these constructs.…”
Section: The Interaction Of Ttg With Rb In the Nucleus Does Not Altersupporting
confidence: 93%
See 4 more Smart Citations
“…In this study we demonstrate that when tTG is localized mostly in the cytosol, it facilitates apoptosis. Further, and in agreement with a previous study (15), we found that the transamidating activity of tTG is necessary for its pro-apoptotic activity in the cytosol. Both membrane and nuclear-localized wild-type tTG did not affect apoptosis, even though thapsigargin treatment resulted in a significant increase in the transamidating activity of these constructs.…”
Section: The Interaction Of Ttg With Rb In the Nucleus Does Not Altersupporting
confidence: 93%
“…However recent studies have provided evidence that tTG can also attenuate apoptosis (14 -16). Interestingly, it has been recently demonstrated that tTG differentially modulates apoptosis in a stimuli-dependent manner (15). This study demonstrated that when the stressor increased the transamidating activity of the enzyme, tTG was pro-apoptotic.…”
mentioning
confidence: 60%
See 3 more Smart Citations